PENTINGNYA WARMING UP DAN COOLING DOWN UNTUK MENGHINDARI CEDERA DALAM OLAHRAGA - Nimrot Manalu; Muhammad Rizki Putra; Steven Parninggotan Pardede; Fendra Ananta Lubis; Muhammad Arif; Andes Martua Harahap (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study evaluates the importance of warming up and cooling down during exercise to reduce the risk of injury. Using qualitative methods through a literature review of journals and scientific articles, it was found that warming up plays a crucial role in physical and mental preparation, improving performance, and enhancing focus. Warming up can be implemented actively through general, dynamic, and preventative movements. Cooling down—whether active (low-intensity) or passive (such as immersing in cold water)—functions to return the body to a calm state, lower the heart rate, and reduce muscle soreness. Therefore, both activities are essential for preventing injury and maintaining long-term fitness.